KETERLIBATAN WORLD WILDLIFE FUND FOR NATURE (WWF) DALAM UPAYA KONSERVASI HARIMAU SUMATERA DI SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING PROVINSI RIAU TAHUN 2010-2014 - Sinamo, Nur Isadah; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about involvement from an international organization named World Wildlife Fund For Nature (WWF) in Sumatera tiger conservation at Bukit Rimbang Bukit Baling, Kuantan Sangingi Riau province. Less of concervation understanding, less of economic, boundary problem, Illegal logging, woods areal conversion into plantations and farms, mine workings, illegal persecution of Sumatera Tiger and less of law have been threatening the Sumatera Tiger population and declining the number of rare every year. As an international organization of conservation based in Swiss who works in environmental issues, biological diversity, and climate change, WWF works together with Riau government to carry out conservation programs such as TPU (Tiger Protection Unit), Tiger Research, Empowerment Comunity, Multilevel Campaign and Regulation Increase at Bukit Rimbang Bukit Baling Concervation.Sources were obtained through literature review from journals, books, mini thesis, reports, and internet to explain WWF’s planned programs. Writer also did some interviews and observations by observing and taking notes of the indications systematically and directly. The theories used in this research are pluralism and green politic theory.This research indicates the reasons involvement of WWF on Sumatera tiger concervation are needed of goverment’s partner on concervation field and urgency of Sumatera tiger on Bukit Rimbang Bukit Baling. WWF got involvement cause of has good funding, has infrastructures for research, and good understanding on wild animals.Keywords: World Wildlife Fund for Nature, Sumatera tiger concervation, involvement, Conservation Program